KNOWING A FOREIGN LANGUAGE OPENS GATES OF FOREIGN COUNTRIES - Berikboyeva Nigora Ravshanovna (American Journals, 2024)
Learning a language is a complex, time-intensive task that requires dedication, persistence, and hard work. If you’re reading this, then you probably already know that.What you might not know is that there are strategies that can help you study more effectively, so that you make the most of your time and energy. This article first explains some of the key principles that guide effective language learning, and then look through that can help you put these principles into practice. Use these tools to create a strategic study plan that helps your language skills grow.
Keywords: Learning codes, false cognates, alternative spelling, Ambiguity or confusion, cultural trends and beliefs.